Analyzing the Development of Structural-Functional Theory in the Sociological Approach to Primary School Education - Imran, M. Muhlis; Shaleh (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2024)
This study investigates the interplay between sociology and education, focusing on Islamic education from a sociological perspective. The objective is to elucidate the sociological dimensions of Islamic education, employing library research for data collection and analysis. This approach facilitated an objective examination of the existing literature, uncovering the multifaceted perspectives within the sociology of education, akin to the diversity in sociological studies. The research underscores the importance of a sociological approach in understanding religious teachings and their social implications, particularly in the realm of Islamic education. It reveals that social issues significantly influence religious teachings, necessitating a comprehensive understanding of social sciences within religious communities. The findings indicate that the sociology of education in the context of Islam incorporates individual, social, and interactional approaches. The individual approach examines personal religious experiences and their educational impact, the social approach considers the influence of societal norms on educational practices, and the interaction approach investigates the interplay between individual beliefs and social contexts in educational settings. This tripartite framework enriches the understanding of Islamic education, highlighting the role of sociological insights in analyzing and interpreting educational phenomena within religious contexts. The study advocates for the integration of sociological theories in educational research, especially for religious education, to unravel the complex interactions between society and education. It proposes that a sociological perspective is essential for a nuanced understanding of Islamic educational practices and theories, urging further research in this interdisciplinary field. The conclusion emphasizes the need for continued exploration of the sociological aspects of education, particularly in Islamic contexts, to foster a more comprehensive and holistic approach to educational studies.